Letters to Frank K. Polk, Chief of the American Commission to Negotiate Peace, at the Crillon Hotel in Paris, from Ó Ceallaigh (1919)
Stating that ‘all American ships approaching Queenstown and other Irish ports are being held up by British torpedo boats and searched’. He also encloses a secret British document which quotes Chief Commissioner W. Edgeworth Johnstone as saying ‘the sailors on all American ships are now suspect, and all their belongings must be searched and a report made in each case’. Also includes a report made by Ó Ceallaigh whereby at a meeting with Polk, the latter stated that any complaint should be made by the aggrieved parties and that there was ‘nothing unusual in customs officials searching sailors entering a foreign port’.